Nurturing Pre-Service and In-Service Education as The Pathway to Fostering The Teacher Leadership Skills - Arwildayanto; Ikhfan Haris; Fory Armin Nawai; Nur Luthfi Ardhiani; Waode Eti Hardiyanti; Jumadi M.S. Tuasikal; Isnanto; Bambang Budi Wiyono; Rusdinal (LPPM Undiksha, 2023)
Professional development is claimed by teachers as urgent, considering that the profession itself refers to a concrete manifestation of a combination of educational legislation, pedagogical theory, and practice in schools. This research aims to analyze the effect of pre-service and in-service education on teacher professionalism. This type of research is qualitative. This study uses a mixed methods approach with a concurrent transformative strategy model. The population includes 251 school principals. The sampling technique used was convenience sampling by distributing questionnaires to 202 returning schools. Data was collected through questionnaires, written tests, interviews, and document studies. Data analysis used Structural Equation Modeling (SEM) and interpretive descriptive models. The results of the data analysis are; first, the influence of pre-service education is significant and positive on teacher leadership. Likewise, the effect on professionalism was also substantial and positive. Second, in-service education is known to significantly and positively impact teacher leadership and professionalism. Third, teacher leadership was found to significantly and positively affect professionalism. It was concluded that pre and service education completely and significantly affected professionalism through teacher leadership. The results of this study can be used as a guideline for increasing teacher professionalism in terms of leadership.